PRELIMINARY REVISIONS OF SOME GENERA OF MALAYSIAN PAPILIONACEAE I - M. S. VAN MEEUWEN; H. P. NOOTEBOOM; C.G.G.J VAN STEENIS (BRIN Publishing (Penerbit BRIN), 1961)
The revisions have been performed by Miss M. S. van Meeuwen (Pycnospora, Smithia, Uraria), H. P. Nooteboom (Galactia, Moghania, Rhynehosia, Stylosanthes, Zornia), and C. G. G. J. van Steenis (Cyclocarpa, Neocollettia).